DEVELOPMENT OF GENDER CULTURE OF WOMEN IN MEDICAL EDUCATION - Ortiqova Nodira Mamajonovna (International Journal of Innovations in Engineering Research and Technology, 2023)
This article analyzes the role of women in the socio-political life of our country on issues of gender policy in medical education, the issues of equal opportunities for women and men in the strategy for achieving gender equality.